Isu dan Permasalahan Keterangan Kanak-Kanak di Bawah Undang-Undang di Malaysia: Satu Penilaian - Mustaffa, Aminuddin; Moharani, Siti Nurul Aziera (Kanun: Jurnal Undang-undang Malaysia, 2012)
This article aims to critically discuss problems and difficulties in extracting evidence from children during court proceedings, with reference to the provisions of relevant statutes in Malaysia. In general, law recognizes the ability as well as the credibility of a child to give evidence in the trial process, provided that he satisfies all the requirements and conditions outlined by the principles of law. However, children, due to their tender age and immaturity, more often than not face difficulties in the process of giving evidence in court. The narration will impact on the process of adducing evidence from the children and consequently affect the credibility or probative value of the evidence tendered. This article shall further provide for some suggestions to be considered in respect of certain imprecision, perceived or otherwise, within the relevant laws. Keywords: children evidence, immaturity, children right, Malaysian Law